Introduction to the special issue "Tibetan tectonics and its effect on the long‐term evolution of climate, vegetation and environment". (4th March 2022) - Tian, Yuntao; Zhuang, Guangsheng; Nie, Junsheng; Xu, Qiang; Xing, Yaowu; Zuza, Andrew; Saylor, Joel; Leary, Ryan; Rohrmann, Alexander
Abstract: The long‐term evolution of the Tibetan Plateau significantly influenced Asian climate, nearby ocean physics and chemistry, and terrestrial biodiversity. This range of impacts has attracted research attention from a correspondingly broad range of disciplines, providing important new insights into prolonged and emerging debates concerning the Himalayan–Tibetan morphotectonic evolution and its impacts on the long‐term evolution of climate, biodiversity, and the environment on regional to global scales. To communicate the latest advances on this coupled tectonic, climatic and biological system, we have launched a special virtual issue in Terra Nova and solicited submissions of 20 papers in total. The papers cover a wide range of topics that fall in the following, partially overlapping, categories: pre‐India–Asia collision tectonic configuration; post‐collision deformation; sedimentary system: source to sink studies, climatic forcing, and river incision; and climatic and biospheric influence of the Tibetan Plateau.